2010
DOI: 10.1007/s12272-010-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive metabolites from the sponge-derived fungus Aspergillus versicolor

Abstract: As part of an ongoing search for bioactive metabolites from the fungus Aspergillus versicolor derived from a marine sponge Petrosia sp., an aromatic polyketide derivative (1), two xanthones (2 and 3), and five anthraquinones (4-8) were isolated by bioactivity-guided fractionation. The gross structures were determined based on the NMR and MS spectroscopic data, and the absolute configurations were defined by comparison of optical rotation data with those of reported. Compounds 2, 4, 5, and 7 exhibited significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 12 publications
5
64
0
Order By: Relevance
“…The cytotoxic concentration of single STC obtained for A549 cells in our study corresponds to a previously reported IC 50 for the same cell line (Bünger et al, 2004;Lee et al, 2010). Pure STC and fungal extracts exerted higher cytotoxic potency towards THP-1 macrophage-like cells, compared to A549 cells.…”
Section: Cytotoxic Potency Of Stc and Stc-producing Aspergilli -Possisupporting
confidence: 86%
“…The cytotoxic concentration of single STC obtained for A549 cells in our study corresponds to a previously reported IC 50 for the same cell line (Bünger et al, 2004;Lee et al, 2010). Pure STC and fungal extracts exerted higher cytotoxic potency towards THP-1 macrophage-like cells, compared to A549 cells.…”
Section: Cytotoxic Potency Of Stc and Stc-producing Aspergilli -Possisupporting
confidence: 86%
“…The structure of 1 was finally determined as nidurufin by 1 H 1 H COSY and HMBC experiments, as well as by comparison with the reported data (Murphy and Cava, 1984). Furthermore, 1 is an optically active compound and has a specific rotation of +157° (c 0.05, MeOH), similar to the reported value (+165°, c 0.07, MeOH) for nidurufin (Lee et al, 2010), which confirmed its structure.…”
Section: Cell Cycle Progression Analysissupporting
confidence: 72%
“…The 9,11-secosteroids 23 – 29 (Liu et al 2014a; Jäälaid et al 2001; Aknin et al 1998; Migliuolo et al 1992; Zhang et al 2013) were isolated from the gorgonian S. suberosa GXBHWZ-22, while 30 (Liu et al 2014b) and 31 (Liu et al 2014a) were synthetic acetylated derivatives of 29 . The anthraquinones 32 – 34 (Lee et al 2010; Chen et al 2014e; Ren and Liu 2011) were isolated from the fungus Aspergillus sp. XS-20090066, 35 – 38 (Slater et al 1971; Arai et al 1989) from the fungus Eurotium sp.…”
Section: Resultsmentioning
confidence: 99%